An observational study on the efficacy of intralesional steroids in patients with idiopathic granulomatous lobular mastitis in a tertiary care centre - Sreekumar, Surabhi; Krishnaswamy, Uma; Kumar, Yasvanth; Vasantham, Sai Sampath Kumar (International Surgery Journal, 2024)
Background: Granulomatous lobular mastitis (GLM) is a rare benign disease of the breast which usually affects young women of childbearing age. The patients usually present with a painful breast mass or with multiple discharging sinuses of breast. Diagnosis is usually established by means of clinical examination followed by radiological, microbiological and histopathological evaluation. The ideal management of patients with GLM is still a matter of debate and treatment modalities such as surgery, systemic and intra-lesional steroids, as well as immunosuppressive agents are being used in clinical practice. In our study, we assessed the clinical response of patients with GLM, treated with intra-lesional steroid injection. Methods: In this prospective observational study, from December 2021 to December 2023, a total of 29 patients who were diagnosed as having GLM and who opted for intra-lesional steroid therapy as the solo treatment, were enrolled. After obtaining informed consent, intra-lesional steroid injection was administered in all the 29 patients. The treatment response was assessed after a period of 3 months from the date of injection. Results: A complete resolution of symptoms and signs was found in majority of the patients (75.9%), 4 (13.8%) had a partial resolution and 2 (6.9%) had persistence of symptoms. One patient (3.4%) was lost to follow up. None had any worsening of symptoms. Conclusions: Intra-lesional steroid can be effectively used in the treatment of GLM and this modality can be completed in a few minutes in an Outpatient setting and is extremely cost effective.